Aspek Piskologi Terhadap Balapan Liar Oleh Remaja - Suardi Suardi; Herman Balla; Fachrul Rijal (Jurnal Litigasi Amsir, 2023)
This study aims to find out what influences adolescents to carry out illegal racing and to find out what law-abiding actions must be done in minimizing teenagers carrying out illegal racing actions. This study uses a normative-empirical research type, which combines theoretical-rational and sensory-observative by using a reasoning model by first using inductive logic which is then continued with deductive logic. The results of the study show that the factors that cause adolescents to carry out illegal racing include factors that are within the child himself, factors that come from the family, factors from the community environment, factors that come from the school environment and efforts made by the Parepare City Police. in tackling illegal racing carried out by teenagers, namely carried out in two ways, namely preventive efforts (prevention) and repressive efforts (enforcement).